2021
DOI: 10.1002/acp.3824
|View full text |Cite
|
Sign up to set email alerts
|

Battling to a draw: Defense expert rebuttal can neutralize prosecution fingerprint evidence

Abstract: The present study examined whether a defense rebuttal expert can effectively educate jurors on the risk that the prosecution's fingerprint expert made an error. Using a sample of 1716 jury-eligible adults, we examined the impact of three types of rebuttal testimony in a mock trial: (a) a methodological rebuttal explaining the general risk of error in the fingerprint-comparison process; (b) a new-evidence rebuttal concluding the latent fingerprint recovered in this case was not suitable for use in a comparison;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Relatedly, recent data from Martire et al (2020) suggest that jurors may be unable-not unwilling-to critically evaluate forensic evidence, such that testimony from an opposing expert and/or judicial instructions may help sensitize them to invalid forensic testimony. Two studies (i.e., Eastwood & Caldwell, 2015;Mitchell & Garrett, 2021) have now found that opposing expert testimony was somewhat effective in this regard, though this question warrants further investigation.…”
Section: Jurors' U Nderstandingmentioning
confidence: 98%
“…Relatedly, recent data from Martire et al (2020) suggest that jurors may be unable-not unwilling-to critically evaluate forensic evidence, such that testimony from an opposing expert and/or judicial instructions may help sensitize them to invalid forensic testimony. Two studies (i.e., Eastwood & Caldwell, 2015;Mitchell & Garrett, 2021) have now found that opposing expert testimony was somewhat effective in this regard, though this question warrants further investigation.…”
Section: Jurors' U Nderstandingmentioning
confidence: 98%
“…However, these findings suggest it could be beneficial to randomize the order of presentation or adjust the order in which the defense and prosecution present when there is a high risk for jurors to be biased away from the presumption of innocence. The most realistic solution would be to make jurors aware of the impact these factors using research-based juror instructions (Garrett et al, 2020), or ensuring that these issues are addressed in the expert's testimony (Mitchell & Garrett, 2021) or cross-examination (Crozier et al, 2020).…”
Section: Discussionmentioning
confidence: 99%